2014
DOI: 10.1038/jcbfm.2014.204
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering of Mitochondrial Cardiolipin Oxidative Signaling in Cerebral Ischemia-Reperfusion

Abstract: It is believed that biosynthesis of lipid mediators in the central nervous system after cerebral ischemia-reperfusion starts with phospholipid hydrolysis by calcium-dependent phospholipases and is followed by oxygenation of released fatty acids (FAs). Here, we report an alternative pathway whereby cereberal ischemia-reperfusion triggered oxygenation of a mitochondria-specific phospholipid, cardiolipin (CL), is followed by its hydrolysis to yield monolyso-CLs and oxygenated derivatives of fatty (linoleic) acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 33 publications
(60 reference statements)
1
39
0
Order By: Relevance
“…total ischemia vs collateral blood flow, may be responsible for the inconsistent results regarding the decrease in phospholipids due to ischemia. Consistent with this argument and the results reported in our study, complete global brain ischemia by decapitation or CA with 7 day-old rats did not significantly decrease the content of phospholipids [11, 13]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…total ischemia vs collateral blood flow, may be responsible for the inconsistent results regarding the decrease in phospholipids due to ischemia. Consistent with this argument and the results reported in our study, complete global brain ischemia by decapitation or CA with 7 day-old rats did not significantly decrease the content of phospholipids [11, 13]. …”
Section: Discussionsupporting
confidence: 93%
“…Some studies showed a significant decrease in the content of brain phospholipids [810, 37], whereas other studies found no change [11, 13], even after 60 min of ischemia [12]. These contradictory findings suggest that ischemia alone is not sufficient to cause significant phospholipid alterations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, a very high level of phospholipid specificity has been discovered as one of the most characteristic features of oxidation reactions triggered by these very different stimuli in different tissues with the common denominator – massive apoptosis. Mitochondrial CLs were found universally and most abundantly oxidized during injury associated with these insults [25, 41, 77, 80, 158]. Strikingly, CL oxidation turned to be non-random as well but had a pronounced specificity unrelated to the pattern of CL polyunsaturation.…”
Section: Selective Cardiolipin Oxidation: Role In Apoptosismentioning
confidence: 99%
“…Mitochondrial membrane depolarization, ROS production, nitric oxide synthase (iNOS) induction, and nuclear translocation of p65 were significantly reduced in latrepirdine-treated rat hippocampal slices subjected to oxygen and glucose deprivation (OGD) followed by reoxygenation (Egea et al, 2014). Another mitochondria-targeted compound, nitroxide electron scavenger (XJB-5-131), prevented cardiolipin oxidation and subsequent hydrolysis, attenuated caspase activation in the brain, and improved neurocognitive outcome when administered after cardiac arrest (Ji et al, 2015).…”
Section: Skqs Decreases Brain Damage After Ischemiamentioning
confidence: 99%